A comparison of Nishida's basho from his middle period with Plato's chóra and the One of Plotinus - Uršič, Marko (Asian studies, 2023)
In this paper, the principal question is the following: How and to what extent can Nishida's basho ("place"), as it is outlined in his famous treatise Basho (1926), taken together with the "adjoining" essay The unsolved issue of consciousness (1927), be understood and interpreted from Plato's and/or Plotinus' (i.e. Neoplatonic) philosophical viewpoint - and, possibly, also vice versa? What do Nishida's conception (or rather intuition) of basho on the one hand, and Plato's quite "vague" concept of chóra in Timaeus and/or Plotinus' first hypóstasis "the One" on the other, have in common? The main formal similarity between basho and "the One" is that they cannot be "predicated" (in the Aristotelian sense) by anything else - or, to put it in Platonic terms, both are absolutely transcendent. However, there are also several important differences, mainly because of the different frames of thought, which are discussed in this paper.
Keywords: basho; chóra; comparative philosophy; Eno; Filozofija; Nishida, Kitaro; Plato; Plotinus; primerjalna filozofija; the One